Sleep duration, sleep quality, and academic functioning among public health students at a university in North Sulawesi - Freysi Heidy Mantiri; Fima Lanra Fredrik Gerarld Langi; Oksfriani Jufri Sumampouw (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Sleep is a fundamental biological need and is one of the main determinants of physical health, cognitive function, and psychosocial well-being. In young adults, including students, sleep patterns often undergo changes due to academic demands, lifestyle, and environmental factors, consequently, insufficient sleep duration and poor sleep quality are common health problems among university students. Neurophysiological mechanisms that link sleep to learning and memory capacity have been widely explained: certain sleep phases support memory consolidation and information processing critical for short- and long-term learning. Purpose: To examine the associations of sleep duration and sleep quality with academic functioning, while assessing academic stress as a potential mediator and physical activity as a potential confounder. Method: An observational study with a cross-sectional approach was employed to evaluate the relationship between sleep duration and sleep quality with the academic function of students at a single time point, taking into account the role of academic stress and health behavior based on the Directed Acyclic Graph (DAG) causal framework and reported in accordance with STROBE guidelines. Results: The relationship between sleep duration and sleep quality with academic function differs according to the type of indicator, where sleep quality is positively associated with motivation to learn (subjective indicators), but does not show significant association with GPA as an objective indicator after multivariate analysis. In addition, there was no meaningful link between sleep and academic stress, and physical activity was not proven to be the main potential confounder that explains sleep relation to objective academic achievement. Overall, sleep has a stronger association on the subjective aspects of academic experience than objective results, and academic stress does not act as a significant mediator, so relationship between sleep and academic functioning are complex and nonlinear. Conclusion: Overall, sleep duration and sleep quality have a stronger association on the subjective aspects of academic functioning such as motivation to learn than objective achievement (GPA), without a significant role of academic stress as mediator or physical activity as the main potential confounder, so that the relationship is complex and nonlinear.